Identification of factors affecting the accident rate in the construction industry. (2017) - Hoła, Bożena; Nowobilski, Tomasz; Szer, Iwona; Szer, Jacek
Abstract: The construction industry is one of the most accident-prone sectors of the Polish economy. There are many causes of accidents and they result from the factors that occur in the working environment. These factors, in favourable circumstances, can significantly increase the probability of a hazard becoming operational and leading to an occupational accident. The article presents the most important factors affecting the development of accidents in the construction industry, which were identified on the basis of surveys. These factors are divided into three groups due to their location in the construction work environment and its surroundings. Mutual relations between the identified factors are graphically presented in the form of the cause and effect diagram of Ishikawa. The relation between the value of construction and assembly production and the accident rate in the construction industry was calculated using the correlation coefficient.